1999
DOI: 10.1097/00005344-199902000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiaggregant and Antiinflammatory Doses of Aspirin on Coronary Hemodynamics and Myocardial Reactive Hyperemia in Conscious Dogs

Abstract: Clinical studies have shown that low doses of aspirin (<300 mg/day) inhibit thromboxane A2 production and platelet aggregation but preserve prostacyclin synthesis. In contrast, high doses of aspirin (>1,000 mg/day) suppress the synthesis of both eicosanoids. Because the consequences of aspirin administration have never been investigated on coronary vasomotor tone in vivo, we investigated the effects of low and high doses of aspirin on systemic and coronary hemodynamics under basal conditions and after myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The mechanisms underlying reactive hyperaemia have been investigated in recent years, with evidence of a role for NO ( Pohl et al ., 1994 ; Gryglewski et al ., 1996 ; Gattullo et al ., 1999 ; Andrieu et al ., 1999 ), prostaglandins ( Messina et al ., 1977 ; Carlsson et al ., 1987 ; Woditsch & Shror, 1992 ; Engelke et al ., 1996 ), adenosine ( Saito et al ., 1981 ; Wei et al ., 1988 ; 1989 ), and K ATP channels ( Daut et al ., 1990 ; Aversano et al ., 1991 ; Lee et al ., 1992 ) mediated vasodilatation. Other studies have shown that K + ATP channels together with prostaglandins ( Viau et al ., 1997 ), adenosine ( Duncker et al ., 1995 ) and NO ( Shinoda et al ., 1997 ) are involved and all act together in mediating the response ( Shinoda et al ., 1997 ; Ishibashi et al ., 1998 ; Kingsbury et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying reactive hyperaemia have been investigated in recent years, with evidence of a role for NO ( Pohl et al ., 1994 ; Gryglewski et al ., 1996 ; Gattullo et al ., 1999 ; Andrieu et al ., 1999 ), prostaglandins ( Messina et al ., 1977 ; Carlsson et al ., 1987 ; Woditsch & Shror, 1992 ; Engelke et al ., 1996 ), adenosine ( Saito et al ., 1981 ; Wei et al ., 1988 ; 1989 ), and K ATP channels ( Daut et al ., 1990 ; Aversano et al ., 1991 ; Lee et al ., 1992 ) mediated vasodilatation. Other studies have shown that K + ATP channels together with prostaglandins ( Viau et al ., 1997 ), adenosine ( Duncker et al ., 1995 ) and NO ( Shinoda et al ., 1997 ) are involved and all act together in mediating the response ( Shinoda et al ., 1997 ; Ishibashi et al ., 1998 ; Kingsbury et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying reactive hyperaemia have been investigated in recent years, with evidence of a role for NO (Pohl et al, 1994;Gryglewski et al, 1996;Gattullo et al, 1999;Andrieu et al, 1999), prostaglandins (Messina et al, 1977;Carlsson et al, 1987;Woditsch & Shror, 1992;Engelke et al, 1996), adenosine (Saito et al, 1981;Wei et al, 1988;1989), and K ATP channels (Daut et al, 1990;Aversano et al, 1991; a b Figure 5 Peak reactive hyperaemic¯ow response (a) and¯ow debt repayment (b) in the presence and absence of glibenclamide. Glibenclamide had a large eect on the peak hyperaemic¯ow response (a).…”
Section: Discussionmentioning
confidence: 99%